A Modified Nonlocal Continuum Electrostatic Model for Protein in Water and Its Analytical Solutions for Ionic Born Models (Communications in Computational Physics, 2013)
A nonlocal continuum electrostatic model, defined as integro-differentialequations, can significantly improve the classic Poisson dielectric model, but is toocostly to be applied to large protein simulations. To sharply reduce the model's complexity, a modified nonlocal continuum electrostatic model is presented in this paperfor a protein immersed in water solvent, and then transformed equivalently as a system of partial differential equations. By using this new differential equation system,analytical solutions are derived for three different nonlocal ionic Born models, where amonoatomic ion is treated as a dielectric continuum ball with point charge either in thecenter or uniformly distributed on the surface of the ball. These solutions are analytically verified to satisfy the original integro-differential equations, thereby, validatingthe new differential equation system.